A Quality Assessment Method of Iris Image Based on Support Vector Machine (Journal of Fiber Bioengineering and Informatics, 2015)
The quality of iris image is one of the key factors in\ruences the performance of iris pattern recognition.\rBased on the existing quality assessment measures of iris image, and in consideration of the most\rprominent factors that lead recognition to fail, we firstly put forward iris rotation which is a new quality\rassessment measure. Then iris rotation, iris visibility, iris eccentricity and iris definition are together as\rquality assessment measures of iris image and the quality assessment of iris image is done by Support\rVector Machine (SVM) classifier. The experiment results express that the method we propose can select\rthe images with good quality and has strong predictability for the performance of iris pattern recognition.
Keywords: Iris Recognition; Quality Assessment; Iris Rotation; SVM Classifier